2020
DOI: 10.1038/s41393-020-00566-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cardiovascular disease risk in individuals with chronic spinal cord injury

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Notably, even a BMI < 22 kg/m 2 can be associated with a percentage of body fat considered obese [ 82 ]. WC may be a better indicator of obesity and cardiovascular risk in SCI patients than BMI and waist-to-hip ratio [ 9 , 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, even a BMI < 22 kg/m 2 can be associated with a percentage of body fat considered obese [ 82 ]. WC may be a better indicator of obesity and cardiovascular risk in SCI patients than BMI and waist-to-hip ratio [ 9 , 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…Obesity has been used to indicate cardiometabolic risk after SCI. In a multicenter study at eight SCI rehabilitation centers in the Netherlands, Dorton et al [ 73 ] identified 257 people with chronic traumatic SCI and compared BMI, WC, and waist-to-hip ratio to cardiovascular disease risk. The authors reported that WC, compared to BMI and waist-to-hip ratio, had the strongest correlation with—and the largest area under—the curve of the Framingham Risk Score 10-year cardiovascular disease risk [ 73 ].…”
Section: Obesity After Scimentioning
confidence: 99%
“…In a multicenter study at eight SCI rehabilitation centers in the Netherlands, Dorton et al [ 73 ] identified 257 people with chronic traumatic SCI and compared BMI, WC, and waist-to-hip ratio to cardiovascular disease risk. The authors reported that WC, compared to BMI and waist-to-hip ratio, had the strongest correlation with—and the largest area under—the curve of the Framingham Risk Score 10-year cardiovascular disease risk [ 73 ]. Mercier et al [ 74 ] reported that obesity (defined as a BMI ≥ 22 kg/m 2 ) was prevalent (82%) and co-occurred with most other CMS risk factors in a retrospective cohort study in 103 adults with SCI.…”
Section: Obesity After Scimentioning
confidence: 99%
“… 1 In persons with SCI, impaired autonomic nervous system (ANS) function gives rise to persistent hypotension and bradycardia, with episodic falls in blood pressure (BP) during orthostatic repositioning (orthostatic hypotension; OH) and severe increases in BP during autonomic dysreflexia (AD). Unmitigated hypotension and OH are associated with cognitive deficits, 2–5 decrease in exercise performance, 6 and adverse changes in health-related quality of life. 7 , 8 There is also an increased risk of stroke 9 and early-onset dementia and Alzheimer's disease in persons with SCI compared to uninjured controls, 10 , 11 which has been associated with impaired cerebrovascular regulation and buffering of BP attributable to loss of integral autonomic hemodynamic regulation.…”
Section: Introductionmentioning
confidence: 99%